1987
DOI: 10.1300/j082v13n04_07
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Among Homosexual Adolescents

Abstract: Little attention has been given in the professional literature to suicide among homosexual adolescents. Sixty-six adolescent psychiatrists responded to a questionnaire on the subject. Results from this survey suggest that many experts are not working with homosexual adolescents. On the other hand, the majority of those treating them considered them to be at higher risk for suicide and agreed that their suicidal gestures were more severe than those of other adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 0 publications
1
32
0
Order By: Relevance
“…If none of the actions taken are able to produce an acceptable (to the individual) outcome, resulting in extreme pressures and stress, a homosexual individual may contemplate or even attempt suicide. There has been evidence linking suicide and homosexual people reporting depression (Kourany, 1987;Kulkin, Chaurin, & Percle, 2000;Skegg, Nada-Raja, Dickson, Paul, & Williams, 2003). At the same time, studies by D'Augelli, Hershberger, and Pilkington (2001) and Remafedi, French, Story, Resnick, and Blum (1998) both found greater suicidal ideation and action in gay men as compared to lesbians, which may reflect the more negative attitude and greater victimization directed toward gay men as compared to lesbians (Pilkington & D'Augelli, 1995).…”
Section: Review Of Existing Evidencementioning
confidence: 97%
“…If none of the actions taken are able to produce an acceptable (to the individual) outcome, resulting in extreme pressures and stress, a homosexual individual may contemplate or even attempt suicide. There has been evidence linking suicide and homosexual people reporting depression (Kourany, 1987;Kulkin, Chaurin, & Percle, 2000;Skegg, Nada-Raja, Dickson, Paul, & Williams, 2003). At the same time, studies by D'Augelli, Hershberger, and Pilkington (2001) and Remafedi, French, Story, Resnick, and Blum (1998) both found greater suicidal ideation and action in gay men as compared to lesbians, which may reflect the more negative attitude and greater victimization directed toward gay men as compared to lesbians (Pilkington & D'Augelli, 1995).…”
Section: Review Of Existing Evidencementioning
confidence: 97%
“…Randomly sampled psychiatrists have reported that the attempts of gay and lesbian adolescents tend to be more severe and lethal than those of heterosexuals. 25 Another descriptive study that rated the severity of attempts made by bisexual/homosexual male adolescents found most attempts to be of moderate to high lethality and limited rescuability, often resulting in hospitalization. Other population-based surveys of adolescents have not ascertained the sexual orientation of respondents, but some have inquired about same-gendered sexual behavior in males.…”
Section: Respondent/nonrespondent Analysesmentioning
confidence: 99%
“…If protective factors were enhanced among GLB youth, suicide in this population is expected to be considerably lower. Protective factors examined here are amenable to change and should be targeted in interventions.Beginning in the 1980s, various reports have indicated an association between a gay, lesbian, or bisexual (GLB) sexual orientation and an increased suicide risk [1][2][3][4][5][6][7][8][9][10][11][12]. The 1989 Report of the Secretary's Task Force on Youth Suicide stated that GLB youth were two to three times more likely to attempt suicide than other young people and might comprise up to 30% of completed youth suicides annually [3].…”
mentioning
confidence: 99%